SIMULATION OF HIGH-VALUE PRODUCT SYNTHESIS: HYDROGEN, METHANE, METHANOL AND DIMETHYL ETHER FROM FLUE GAS - Mungkalasiri, Woranee; Ponglumjeakngam, Patsariya; Iamlek, Sukasama; Mungkalasiri, Jitti (Srinakharinwirot University Journal of Sciences and Technology, 2023)
The solid oxide electrolysis cell (SOEC) is an electrochemical device that can efficiently convert carbon dioxide and steam to syngas using flue gas from industrial processes. Syngas can be used to produce various fuels such as methane, methanol and dimethyl ether. Therefore, this research aims to study the production of hydrogen from a solid oxide electrolysis cell system. Flue gas from a coal power plant was used to produce hydrogen. Then, hydrogen was used as a main feed component in methane synthesis, methanol synthesis and dimethyl ether synthesis. These processes were designed and simulated by using Aspen Plus V.11. The developed model was employed to study the optimal operating conditions of each process. In this study, flue gas from a coal power plant was fed into SOEC with 200 l/hr. The influences of variables affecting the operation of each process were studied. The simulation results showed that the optimal operating conditions for SOEC were temperature of 800oC and pressure of 1 bar. The maximum amount of hydrogen was 3.261 kmol/hr. The optimal operating conditions for methane synthesis were temperature of 100oC, pressure of 30 bar, H2/CO ratio of 1 and H2/CO2 ratio of 4. The maximum amount of methane was 1.630 kmol/hr. The optimal operating conditions for methanol synthesis were temperature of 200oC, pressure of 100 bar, H2/CO ratio of 2 and H2/CO2 ratio of 4. The maximum amount of methanol was 1.435 kmol/hr. The optimal operating conditions for dimethyl ether synthesis were temperature of 140oC, pressure of 20 bar, H2/CO ratio of 1 and H2/CO2 ratio of 2. The maximum amount of dimethyl ether was 1.287 kmol/hr. Furthermore, the results from this study revealed that flue gas or waste gas produced from power plant or other industries can be reused to produce high value-added products which according to circular economy concept.